Life and Death of mRNA Molecules in Entamoeba histolytica - Valdés-Flores, Jesús; López-Rosas, Itzel; López-Camarillo, César; Ramírez-Moreno, Esther; Ospina-Villa, Juan D.; Marchat, Laurence A. (Frontiers in Cellular and Infection Microbiology, 2018)
In eukaryotic cells, the life cycle of mRNA molecules is modulated in response to environmental signals and cell-cell communication in order to support cellular homeostasis. Capping, splicing and polyadenylation in the nucleus lead to the formation of transcripts that are suitable for translation in cytoplasm, until mRNA decay occurs in P-bodies. Although pre-mRNA processing and degradation mechanisms have usually been studied separately, they occur simultaneously and in a coordinated manner through protein-protein interactions, maintaining the integrity of gene expression. In the past few years, the availability of the genome sequence of Entamoeba histolytica, the protozoan parasite responsible for human amoebiasis, coupled to the development of the so-called “omics” technologies provided new opportunities for the study of mRNA processing and turnover in this pathogen. Here, we review the current knowledge about the molecular basis for splicing, 3′ end formation and mRNA degradation in amoeba, which suggest the conservation of events related to mRNA life throughout evolution. We also present the functional characterization of some key proteins and describe some interactions that indicate the relevance of cooperative regulatory events for gene expression in this human parasite.